PENGAWETAN DAN PENGOLAHAN LIMBAH IKAN SERTA IKAN SEGAR MENJADI PRODUK YANG DAPAT MENINGKATKAN PENDAPATAN KELUARGA NELAYAN DI KELURAHAN MALABRO KOTA BENGKULU - Madani Hatta; Halimatusyadiah .; Novita Sari (Universitas Bengkulu, 2014)
This program is a community service activities with the activity of the title isPreservation and Processing of Fish Waste and Fresh Fish that can be Income GeneratingProducts for Fishermen Household in Village Malabro Bengkulu. This activity aims toequip the housewives of fishermen about fish preservation and processing of fish wasteinto products that can be sold to raise additional revenue for fishermen family in thevillage of Malabro. The results achieved from this activity is fishermen housewives havegained new knowledge about fish preservation and processing of fish waste into fishcrackers, fishermen housewives eager and motivated to immediately apply the knowledgeand skills gained from this activity, establishment of home industry by housewives offishermen engaged in the processing of fish crackers processed fish waste, fishermenhousewives have been able to preserve the fish in order to survive longer, fishermenhousewives have learned how to market their product or distributed crackers they made,which has been formed a new source of income for women in the fishing village Malabro.Keyword: Preservation, Processing, Fish Waste, Fish Crackers